PENGARUH KOMUNIKASI ANTARA ORANG TUA DENGAN ANAK DAN MINAT BELAJAR TERHADAP HASIL BELAJAR EKONOMI PADA SISWA MADRASAH ALIYAH NEGERI (MAN)1 PESISIR SELATAN - Devi Edriani (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
This study aims to analyze and see the effect of Communication between parents with children and interest in economic learning of economic learning outcomes in students MAN 1 Pesisir Selatan.The type of this research is descriptive and associative research. The study population was all students of MAN 1 Pesisir Selatan which amounted to 301 people, the sample number was 172 people.The sampling technique is done by proportional random sampling.The data source is primary data and secondary data, primary data in the form of questionnaire that is run on the respondent, while the secondary data is about student learning outcomes obtained from the documentation.Test the instrument using validity and reliability test.Data analysis using descriptive analysis and inductive analysis, namely normality test, heterokedastisity test and multicollinearity test, data analysis using multiple regression analysis and hypothesis test using F test and t test.The results showed that: 1) Communication between parents with children significantly influence the students' economic learning outcomes2) Interest in economic learning has a significant effect on students' economic learning outcomes3) Communication between parents with children and interest in economics have a significant effect on student learning outcomes